Prevalence of Borderline Personality Disorder in University Samples: Systematic Review, Meta-Analysis and Meta-Regression. - Rebecca Meaney; Penelope Hasking; Andrea Reupert; Andrea Reupert (PLoS ONE, 2016)
Objective To determine pooled prevalence of clinically significant traits or features of Borderline Personality Disorder among college students, and explore the influence of methodological factors on reported prevalence figures, and temporal trends. Data sources Electronic databases (1994-2014: AMED; Biological Abstracts; Embase; MEDLINE; PsycARTICLES; CINAHL Plus; Current Contents Connect; EBM Reviews; Google Scholar; Ovid Medline; Proquest central; PsychINFO; PubMed; Scopus; Taylor & Francis; Web of Science (1998-2014), and hand searches. Study selection Forty-three college-based studies reporting estimates of clinically significant BPD symptoms were identified (5.7% of original search). Data extraction One author (RM) extracted clinically relevant BPD prevalence estimates, year of publication, demographic variables, and method from each publication or through correspondence with the authors. Results The prevalence of BPD in college samples ranged from 0.5% to 32.1%, with lifetime prevalence of 9.7% (95% CI, 7.7-12.0; p < .005). Methodological factors contributing considerable between-study heterogeneity in univariate meta-analyses were participant anonymity, incentive type, research focus and participant type. Study and sample characteristics related to between study heterogeneity were sample size, and self-identifying as Asian or "other" race. The prevalence of BPD varied over time: 7.8% (95% CI 4.2-13.9) between 1994 and 2000; 6.5% (95% CI 4.0-10.5) during 2001 to 2007; and 11.6% (95% CI 8.8-15.1) from 2008 to 2014, yet was not a source of heterogeneity (p = .09). Conclusions BPD prevalence estimates are influenced by the methodological or study sample factors measured. There is a need for consistency in measurement across studies to increase reliability in establishing the scope and characteristics of those with BPD engaged in tertiary study.